(untitled) (Studia austriaca, 2017)
In his novel Der fliegende Berg, Christoph Ransmayr plays with seemingly contradictory myths that surround the Himalayan mountain Phur-Ri, a mountain that is not marked on any maps and symbolizes a void, a figment of the imagination that serves as a foil for unfulfilled longings and desires. Using Roland Barthes and Mircea Eliade as its theoretical framework, this article analyzes the function of myths in Ransmayr’s novel and explores whether his use of myth can fill the void with meaning – or whether the void remains a vacuum that repells rather than allows for any form of signification.